Antioxidant Activity of Tahongai Leaves (Klenhovia hospital L.) Infusa Using DPPH Method - Leswana, Nurillahi Febria; Sianturi, Sister (JURNAL PROTEKSI KESEHATAN, 2024)
Tahongai plant (Kleinhovia hospita Linn.) is a plant that grows naturally on the edge of Indonesian rivers, especially in East Kalimantan. Tahongai plants are used as medicine by the Dayak people in Kalimantan, namely that empirically the use of tahongai plants is effective as a medicine that can treat various diseases such as jaundice, hypertension, diabetes, and cholesterol by drinking the boiled water. The active substances contained in tahongai leaves are saponins, flavonoids, and alkaloids are expected to have antioxidant activity. The purpose of this study was to measure the antioxidant activity of tahongai leaf infusa. The extraction method used in this study was infusa while the radical specimen used was DPPH with Vitamin C as the comparison. Phytochemical screening was also carried out ontahongai leaf infusa extract positively containing flavonoids, tannins, saponins and phenols. Based on the results of the DPPH radical scavenging analysis of Tahongai leaf infusion, the IC50 value was 139.51 mg/L with the medium antioxidant activity.